Environmental Representation and Human-Nature Relations in Ozi: Voice of The Forest (2023) - Jovial Sebastian Paranga; Putri Ayienda Dinanti; Daffa Afif Nabillah (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
Human activities have an impact on the environment and nature, especially through the exploitation of resources that threaten the sustainability of the ecosystem. This issue is often raised in audiovisual works, including animated films, as a medium to convey social and ecological criticism. This study aims to reveal the representation of environmental issues in the animated film Ozi: Voice of the Forest (2023) based on six concepts of ecocriticism by Greg Garrard: pollution, wilderness, apocalypse, dwelling, animals, and earth, and also analyze the depiction of relationship between humans and nature through the perspectives of anthropocentrism and ecocentrism. This study uses a descriptive qualitative method by collecting data through observations of scenes and dialogues in the film. The results of the study show that contemporary animated films such as Ozi: Voice of the Forest (2023) can convey issues related to environmental destruction caused by humans due to an anthropocentric perspective that exploits nature, but also simultaneously presents an ecocentric perspective through efforts to maintain ecological balance and a harmonious relationship between humans and nature.